2015
DOI: 10.5152/tud.2015.98475
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the correlation between sperm DNA integrity and conventional semen parameters in infertile men

Abstract: Objective: A male factor is responsible in approximately 30-40% of couples receiving infertility treatment. Routinely, such couples undergo semen analysis including parameters such as sperm count, motility and morphology. Generally, the analysis of sperm DNA damage, shown to have a significant clinical importance by many studies, is recognized as an advanced test that is not included in routine infertility tests. Intracytoplasmic sperm injection method, commonly employed in the current infertility treatment pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 34 publications
2
16
1
1
Order By: Relevance
“…2 B) can damage normal regulation of sperm functions such as sperm capacitation, acrosome reaction, and sperm-oocyte fusion 18,19 . It has been reported that ROS can attack the DNA in sperm nucleus causing base modification, DNA damage, and chromatin cross-linking 20,21 , similarly found in our result (Fig. 4 B).…”
Section: Fig 4: No Dna Damage In Testes Of Control Male Mice (A) Andsupporting
confidence: 91%
“…2 B) can damage normal regulation of sperm functions such as sperm capacitation, acrosome reaction, and sperm-oocyte fusion 18,19 . It has been reported that ROS can attack the DNA in sperm nucleus causing base modification, DNA damage, and chromatin cross-linking 20,21 , similarly found in our result (Fig. 4 B).…”
Section: Fig 4: No Dna Damage In Testes Of Control Male Mice (A) Andsupporting
confidence: 91%
“…34 The inverse correlated of Sperm DNA fragmentation with the total motility and normal morphology of spermatozoa, could be the reason of subfertility in the patient groups. [36][37][38] Significantly positive correlation recorded between seminal OS, LPO and DNA fragmentation in our study suggests that the observed LPO and DNA damage may have been due to increased ROS production. The high susceptibility of spermatozoa to OS-induced DNA damage can result not only in poor fertilization rates but also lead to poor embryo quality which can cause birth defects and even childhood diseases.…”
Section: Correlation Between Seminal Redox Status and Sperm 4-hne Dnmentioning
confidence: 84%
“…It was interesting to observe significantly higher %DFI in male factor infertility, indicating that sperm DNA integrity was compromised in these cases. Earlier studies have also reported significantly higher sperm DNA damage in male factor infertility compared to normal men (Høst et al 2000, Saleh et al 2002, Aydos et al 2015, highlighting the significance of sperm DNA integrity as an important factor in male fertility. Another interesting finding was that the concentration of free thiols, an indicator of less highly condensed chromatin, was significantly higher in the unknown factor infertility group compared to the male factor infertility group.…”
Section: Discussionmentioning
confidence: 82%